Evaluation of electronic medical records implementation in outpatient services at the Hospital using MMUST Framework - Asri, Dinda Isnaini; Budi, Savitri Citra (Universitas 'Aisyiyah Yogyakarta, 2025)
The implementation of electronic medical records (EMR) is mandatory in Indonesia to improve efficiency and service quality. However, challenges remain in information quality and facility conditions. This study employed a mixed-methods approach with a concurrent embedded design, conducted from June to September 2024. Quantitative data were collected through a survey of 116 outpatient EMR users and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.0.6. Qualitative data gathered through interviews, were analyzed thematically. The result showed that five out of six hypotheses were accepted. Information quality significantly influenced information satisfaction, performance expectations, attitude, overall satisfaction, and net benefits. However, facility conditions did not significantly affect attitude. Qualitative findings confirmed these results and emphasized the importance of information quality, ease of access, efficiency, and infrastructure improvements in ensuring system effectiveness. EMR implementation is beneficial but requires improvements in system usability, facility support, and periodic evaluation are necessary.